Protein kinase D interacts with adaptor protein Ruk/CIN85 and phosphorylates it - Yu. A. Rzepetsky; A. A. Samoylenko; O. P. Kukharenko; S. V. Mikhalap; S. P. Sidorenko; A. Hausser; L. B. Drobot (Біологічні студії, 2009)
Adaptor protein Ruk/CIN85 is built of multiple domains and motives involved in the intermolecular interactions. It functions as a key component of signalling networks that controls important cellular responses in coordinated fashion. The presence of many consensus motives for a number of protein kinases in Ruk/CIN85 structure suggests that phosphorylation is one of the most probable adaptor protein posttranslational modifications capable of regulating its biological activity depending on cellular context. In this study, we have demonstrated that protein kinases D (PKD) 1 and 2 co-immunoprecipitate with Ruk/CIN85 from lysates of HEK293 cells transiently transfected with pRc/CMV-Rukl vector. By using the panel of Ruk/CIN85 GST-fusion fragments for PKD2-Flag precipitation, it was shown that PKD2 interacts with SH3В and, to a less extent, with SH3С Ruk domains, while the simultaneous presence of both domains enhances this interaction. It was also found that PKD2 most strongly interacts with Pro-rich region of Ruk and possesses considerably lower affinity to coil-coiled domain. The results of in vitro kinase assay using anti-PKD2-Flag immunoprecipitates and GST-fusion forms of Ruk SH3 domains, as substrates showed that the highest level of radioactive 32Р incorporation from [γ-32P]ATP was observed in SH3AB fragment comparing with considerably lower intensity of SH3ABC and SH3B phosphorylation. The obtained data suggest that PKD is a novel binding partner forof Ruk/CIN85 involved in the control of its functional activity through phosphorylation.